PANDANGAN FILOSOFIS TERHADAP KEBIJAKAN MERDEKA BELAJAR ANTARA KEBEBASAN DAN TANGGUNG JAWAB DALAM PENDIDIKAN - Fairuzy, Lulie Hana; Sendy Annafi Rizqi; Salsa Bella Anisa; Munbaits, Tika Bilqis (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This article aims to explore the philosophical perspectives on the "Merdeka Belajar" (Independent Learning) policy in the context of freedom and responsibility in education. Using a qualitative approach through literature analysis, this article delves into the philosophical concepts of freedom and responsibility from educational thinkers such as Ki Hadjar Dewantara, Paulo Freire, and John Dewey, while evaluating the implementation of this policy in Indonesia. The results show that the "Merdeka Belajar" policy has had a positive impact on student motivation for independent learning, but still faces challenges in implementation, such as insufficient understanding by teachers and limited infrastructure support. The discussion highlights that the freedom offered in education must be balanced with responsibility from students, teachers, and parents to create an effective learning environment. In conclusion, despite the challenges, this policy holds significant potential to shape a generation of learners who are intelligent, critical, and responsible.